Complete mitochondrial genomes of the “Acmaeidae” limpets provide new insights into the internal phylogeny of the Patellogastropoda (Mollusca: Gastropoda) - Putri, Eggy Triana; Lee, Damin; Kwak, Haena; Kim, Yukyung; Nakano, Tomoyuki; Park, Joong-Ki (Frontiers in Marine Science, 2023)
The subclass Patellogastropoda (called “true limpets”) is one of the most primitive groups of the Gastropoda and contains approximately 350 species worldwide. Within this subclass, internal phylogeny among family members, including relationships of the “Acmaeidae” with other patellogastropod families, remains incompletely clarified. Here, we newly determined two complete mitochondrial genome sequences of “Acmaeidae” (Acmaea mitra and Niveotectura pallida) and one sequence from Lottiidae species (Discurria insessa) and combined them with mitochondrial genome sequences of 20 other published limpet species for phylogenetic analysis of the sequence dataset (nucleotides and amino acids) of 13 protein-coding genes using maximum likelihood and Bayesian inference methods. The resulting phylogenetic trees showed monophyly of Patellogastropoda species that were subsequently subdivided into two clades [clade I (Nacellidae, Pectinodontidae, Acmaeidae, and Patellidae) and clade II (Eoacmaeidae and Lottiidae)]. The sister relationship between the Acmaeidae and Pectinodontidae species revealed by phylogenetic analysis was also supported by sharing their similar gene arrangement patterns, which differ substantially from those of clade II members including the Lottiidae species. The polyphyletic relationship between Acmaeidae (grouped with Pectinodontidae as a sister taxon in clade I) and Lottiidae species (grouped with Eoacmaeidae in clade II) corroborates that they are phylogenetically distinct from each other. This mitochondrial genome phylogeny contradicts previous morphology-based hypotheses, yet highlights that Acmaeidae and Pectinodontidae are the most closely related. Further in-depth analysis of the complete mitochondrial genome sequences based on a broad range of samples including those from relatively unstudied and/or underrepresented taxa is required to fully understand the mitochondrial genome evolution and a more comprehensive phylogeny among the major groups of the Patellogastropoda.